Biodiesel, processing and characteristics - Farid Nasir Ani; Motasemi, Farough; Faraji, Soheila (Penerbit UTM Press, 2016)
The book begins with an introduction to the range of issues associated with fossil fuel reserves as well as issues related to the environment. Among the issues, is the supply of petroleum resources are dwindling, global, warming and the rise in petroleum prices volatile. In addition, it also lead to the introduction to the types of waste oil as well as its characteristics.